Development of interactive hologram-based learning media for physical education sports and health subjects in elementary school - Lastya, Saeldho We; Budi, Didik Rilastiyo; Festiawan, Rifqi; Kusnandar, Kusnandar; Estrella, Erwin O.; Khan, Mohammad Ashraf (Indonesian Journal of Research in Physical Education, Sport, and Health, 2025)
Background: Physical education sports and health material sports games still use conventional methods by relying on books and other tools. Technology-based interactive media has yet to be applied to interactive learning. Objective: This study aims to produce hologram-based interactive learning media that effectively increase student knowledge. Methods: This study used the Research and Development (RnD) method. This study used a sample of 5th-grade students from State Elementary School 1 Tinggarwangi 26 students, State Elementary School 3 Jambu 16 students, and State Elementary School 1 Banteran 20 students. Research instruments for media use validation questionnaires and student and teacher assessments. Cognitive aspect research instruments use questions that previously passed the validity stage. The data analysis technique uses quantitative description, including Normalits, Homogeneity, and T-tests. Result: Based on the assessment results from media experts, material experts, linguists, teachers, and students, the earning media produced a feasible category for the learning process. The effectiveness test results show that interactive learning media effectively increases students' knowledge. Conclusion: Interactive learning media for big and small ball games is very feasible for use as learning media for elementary/equivalent students.